161k views
4 votes
Evaluate b^2c^-1 for b=8 and c=-4

User Emprice
by
4.9k points

2 Answers

4 votes

For this case we must evaluate the following expression:


(b ^ 2) (c ^( -1))

When
b = 8 and
c = -4

By power properties we have to:


a ^ {-1} = \frac {1} {a ^ 1} = \frac {1} {a}

Then, we can rewrite the expression as:


(b ^ 2) * (\frac {1} {c}) = \frac {b ^ 2} {c}

Substituting the values we have:


\frac {8 ^ 2} {- 4} = \frac {64} {- 4} = - 16

Answer:

-16

User Kimbaudi
by
4.8k points
2 votes

Answer:

-16

Explanation:

b^2 *c^-1

Let b=8 and c=-4

(8)^2 * (-4)^-1

The negative exponent goes to the denominator

64 * 1/(-4)^1

64 *1/(-4)

-16

User Parek
by
5.8k points